Stock Market Volatility and Corporate Investment - Hu, Zuliu (IMF Working Papers; Working Paper ;, 1995)
Despite concerns are often voiced on the so called 'excess volatility' of the stock market, little is known about the implications of market volatility for the real economy. This paper examines whether the stock market volatility affects real fixed investment. The empirical evidence obtained from the US data shows that market volatility has independent effects on investment over and above that of stock returns. Volatility and its changes are negatively related to investment growth. To the extent volatility depresses fixed capital formation and hence future income growth, the results suggest the desirability of reducing stock market volatility.